Urachal Villous Adenoma Coexistent With Urachal Carcinoma: A Case Report - Shotaro Hatano; Yousuke Shimizu; Hirotake Fujii; Koken Hayashi; Ken Maekawa; Yasuyuki Miyauchi; Takaki Sakurai; Kenji Mitsumori; Hiroyuki Onishi (IJU Case Reports)
ABSTRACT Introduction Urinary tract villous adenomas are uncommon, urachal villous adenomas being especially rare. While their malignant potential remains uncertain, villous adenomas may have malignant components. Here, we present a case of the coexistence of a urachal villous adenoma and urachal carcinoma. Case Presentation We report the case of an 86‐year‐old woman with a urachal tumor of the bladder wall. A biopsy yielded a diagnosis of villous adenoma. Because of the possibility of coexisting malignancy, we performed a partial cystectomy, including excision of the umbilical ligament. Examination of the operative specimen revealed mucinous adenocarcinoma. She has remained recurrence‐free for 8 months postoperatively. Conclusion We here report the coexistence of a villous adenoma and mucinous adenocarcinoma of the urachus. Because urachal villous adenomas can have malignant components, they require aggressive treatment. This rare combination should be kept in mind.